TA’LIIM AL-LUGHAH AL-‘ARABIYYAH LI AL-THULLAB AL-WAFIDIIN FII JAMI’AH AL-MALIK SAUUD BI AL-RIYADH AL-MAMLAKAH AL-‘ARABIYYAH AL-SAUUDIYYAH - Hamid, Hamid (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
The interesting finding of this research is the model of teaching Arabic for foreign student developed by Malik Sauud University, Riyadh, Saudi Arabia. In the past, the teaching Arabic for foreign student or non-native in Arab mostly used direct method, while in this research it is found out that there are five important things in teaching Arabic language. The first, the Arabic language teaching needs specific dormitory for the foreign students so that all of the program can be applied exclusively. Second, the direct method , is still applied completed with communicative approach and various strategies. Third, the use of multi-media is considered important eventough the tutors are native speaker. This also shows that teacher-centered has shifted into student-centered sothat teachers take role as facilitator. Fourth, the materials presented are suited with Arabic culture and the culture of students’ origin. Fifth, the phase of evaluation is considered most important to measure the success of learning Arabic language. The shift of language learning model of Arabic language in Arab country as applied in Malik Sauud University, Riyadh, Arab Saudi can be a new trend in developing Arabic language and culture teaching learning.Keywords: Ta’liim, Jami’ah Al-Malik Sauud